Schuylkill Valley Paper - The Mesabi Iron-Range - Horace V. Winchell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1893)
This paper, embodying information acquired by the writer in his work in connection with the Geological Survey of Minnesota, is presented by permission of the State Geologist. Historical.—On November 16, 1890, the workmen of Captain J. A. Nichols, of Duluth, Minn., encountered in a test-pit on the northwest quarter of section 3, township 58, range 18, west of the fourth principal meridian, the body of soft ore now called the Mountain Iron mine. Hard ore, chiefly magnetic, had been known for many years on the Mesabi range, and explorations made by Mr. E. W. Griffin, of Minneapolis, near the falls of Prairie river in T. 56-24 and T. 56-25, and by John Mallmann, at the Mallmann explorations, T. 59-14, had revealed some hard hematite interbedded with quartzite and low-grade soft ore; but this was the first discovery of merchantable hematite on the range. Captain Nichols had been exploring more or less along the range for some two years. To him and to the Merritt brothers, of Duluth and Oneota, who, unshaken in Faith by the discouraging reports of explorers, miners, experts, and geologists, had persevered in the search for ore, great credit is due for the final success, and large rewards have accrued to them already.